Database of processing techniques and processing factors compatible with the EFSA food classification and description system FoodEx 2: Objective 1: Compendium of Representative Processing Techniques investigated in regulatory studies for pesticides. Issue 11 (26th November 2018) - Scholz, Rebekka; Herrmann, Michael; Kittelmann, Arno; von Schledorn, Maria; van Donkersgoed, Gerda; Graven, Coen; van der Velde‐Koerts, Trijntje; Anagnostopoulos, Chris; Bempelou, Eleftheria; Michalski, Britta
Abstract: EFSA is conducting pan‐European dietary exposure and risk assessments related to actual levels of pesticide residues in food commodities. These assessments use the pesticide occurrence data generated under the official monitoring programs of Member States, the consumption data from EFSA's comprehensive food consumption database and pesticide‐specific information such as processing factors. Currently no harmonised list of processing factors is available within Europe and worldwide. The overall objective of this project is to develop a database of validated processing factors based on the residue definitions for enforcement, which is compatible with the EFSA food classification and description system FoodEx 2. In the first part of the project, a compendium of representative processing techniques is elaborated as a standard description of all relevant processes and basis for validation of processing studies. The compendium of processing techniques is built upon a selection of representative and up‐to‐date processing studies submitted in the context of regulatory procedures for plant protection products. It covers the most important processes in food processing, both with respect to importance in consumption and production. Though not really considered as processing operations, peeling and pitting procedures are included in this compendium. For each process, a typical set of processing conditions is provided based on published literature and/or inquiry in the food processing industry. Detailed descriptions of processing conditions and yield factors for the processes are given. The processes are visualised in flowcharts. Processing studies are conducted on a very limited number of representative commodities. Extrapolation proposals are made based on the comparability of processing conditions, the plant anatomy and the plant part to be processed.